TESTING THE CAPITAL ASSET PRICING MODEL AND SENTIMENT ON STOCKS LISTED ON THE INDONESIA STOCK EXCHANGE - Zainul, Zaida; Nurhalis; Fathurrahman Anwar; Sophia Imari (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The Capital Asset Pricing Model (CAPM) provides a strong theoretical foundation for understanding stock returns; however, the dynamics of modern financial markets indicate that stock price movements are influenced not only by market risk but also by psychological factors, particularly sentiment. This study aims to analyze the effects of market risk premium, investor sentiment, and market sentiment on excess stock returns of companies listed on the Indonesia Stock Exchange (IDX). The sample consists of 93 companies listed on the IDX during the 2013–2023 period. Panel data regression analysis using the Common Effect Model is employed to test the research hypotheses. The results show that the market risk premium and investor sentiment have a positive and significant effect on excess stock returns in Indonesia. However, market sentiment does not have a significant effect on excess stock returns. These findings enrich the theoretical understanding of the relevance of the Capital Asset Pricing Model and stock market behavior in Indonesia. For investors, investment timing strategies can be implemented based on changes in market sentiment and market risk premium conditions to maximize potential returns.